Diagnosis & advice in the undulating strokes - Persyn, U.; Colman, V.; Ungerechts, B. (coachesinfo.com, 2000)
The locomotion and the physical characteristics of breaststroke and butter-fly swimmers us-ing the most undulating and the flattest variants will be compared. There is much more velocity variation of the centre of mass of the body in the flattest than in the most undulating variants. In the most undulating variants, during the largest part of the arm propulsion, a relatively small increase in velocity occurs. During the last part of the arm propulsion and the first part of the arm re-covery, the velocity is relatively well maintained. During the first part of the bottomward leg kick, an early increase in velocity occurs. In butterfly higher flexibility scores corre-spond with more undulation. The individual undulation in butterfly is indicative for the best undulation in breaststroke. Flexibility and strength determine the best stroke and style variant per individual with a mean error in per-formance calculation of less than 3%.